OPTICAL AND MAGNETO-OPTICAL PROPERTIES OF PERMALLOY THIN FILMS IN 0.7–6.4 eV PHOTON ENERGY RANGE. (15th January 2017) - Tikuišis, Kristupas Kazimieras; Beran, Lukášs; Cejpek, Petr; Uhlířová, Klára; Hamrle, Jaroslav; Vaňatka, Marek; Urbánek, Michal; Veis, Martin
Abstract: Permalloy is a widespread material used in numerous fundamental experiments and novel spintronic, optoelectronic devices. In order to model their response or tailor the optimal experimental parameters it is necessary to know the optical and magneto-optical properties of this material over a wide spectral range. We report on the systematic study of optical and magneto-optical properties of 10 nm and 150 nm thick permalloy films by means of spectroscopic ellipsometry and magneto-optical spectroscopy. To study the influence of the surface oxidization, the samples were prepared with and without Au capping layer. Spectral dependence of the complete permittivity tensor was derived from experimental data in a broad spectral range covering IR, visible and UV regions. All samples exhibited metallic-like optical and magneto-optical properties with clear differences in 10 nm thick bare sample. These differences to overall optical and magneto-optical properties of nanometer-thick permalloy layers were ascribed to a strong influence of the surface oxide. Graphical abstract: Highlights: spectral dependence of the complete permittivity tensor of permalloy thin films has been derived in broad spectral range from 0.7 to 6.4 eV required for theoretical design of novel optoelectronic devices; influence of the surface oxidization on the optical and magneto-optical properties of uncapped nanometer-thick permalloy films have been demonstrated; spectral dependence of polar Kerr magneto-optical effect and its variation with permalloy layer thickness has been demonstrated to be used for fine-tuning experimental parameters or device geometry; influence of the substrate/layer interface to the magneto-optical properties have been demonstrated in 10 nm thick permalloy film.